A hedonic analysis of the value of parks and green spaces in the Dublin area - Karen Mayor; Seán Lyons; David Duffy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2009)
We use a hedonic house price model to estimate the value of green spaces and parks to homeowners in the Dublin area. Using a dataset of house sales between 2001 and 2006 and combining it with available data on the location of green spaces in Dublin it is possible to assess the different values assigned to green areas by homeowners. We find that the value of green space depends first of all on how far from the property it is located. We also find a difference in the values assigned to open access parks and green spaces. For every 10% increase in the share of green space and park area near a house, its average price increases by 7% to 9%. We also attempted to identify different individual parks and rank them according to their value, however due to spatial multicollinearity the results were mixed.
Keywords: 330; hedonic regression; green spaces; urban parks; Ireland; Immobilienpreis; Wohnimmobilien; Grünfläche; Hedonischer Preisindex; Regression; Dublin; Irland